Kajian Waralaba Bibit Kelapa Sawit di Bengkulu - Tatik Raisawati; Edi Susilo; Susi Handayani (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2013)
The increasing of the area smallholding following by increasing necessity of oil palm seeds. The problem with increasing necessity of oil palm seeds is availibility of seeds. The use of illegitime seeds is still common particularly by smallholders who have difficulties in obtaining high quality seeds. The government will is establishing franchishing system (known as waralaba bibit) therefore make special effort to improve the appreciatian of the smallholder on benefits of legitime seeds and to make them easier available. This paper thus highlights the study of franchise of oil palm seed in Bengkulu. The study showed the distribution of the seed have enjoyed by smallholders. While the analysis economic through R/C ratio for franchise oil palm seed without rent land is 2,31 and franchise oil palm seed with rent land is 2,12. It sees both of them are benefit.